1999
DOI: 10.1037/h0080409
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian identity development: An examination of differences across generations.

Abstract: Lesbian identity is an achieved, not an ascribed, status. Family, social, and historical circumstances affect the timing, sequence, and outcome of this developmental process. The life stories of 31 women, identified within three eras of lesbian history, demonstrate the critical role of history in understanding lesbian identity and experience today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…Understanding the implications of such differences is essential to assess the interactions between individuals, social groups, and changing social structures and contexts (Fredriksen-Golden et al, 2010). Among literature exploring birth cohort (Parks, 1999;Rosenfeld, 1999) differences and maturational factors, it remains evident that the larger social context (Floyd & Bakeman, 2006), plays a significant role in sexual identity development. Dividing older LGBT adults into age groups or identity cohorts (Parks, 1999;Rosenfeld, 1999) provides insight with regard to differing perspectives on the need for advocacy, issues related to social justice (employment, housing, relationships, etc.…”
Section: Life Span Identity Development and Age Cohortsmentioning
confidence: 99%
“…Understanding the implications of such differences is essential to assess the interactions between individuals, social groups, and changing social structures and contexts (Fredriksen-Golden et al, 2010). Among literature exploring birth cohort (Parks, 1999;Rosenfeld, 1999) differences and maturational factors, it remains evident that the larger social context (Floyd & Bakeman, 2006), plays a significant role in sexual identity development. Dividing older LGBT adults into age groups or identity cohorts (Parks, 1999;Rosenfeld, 1999) provides insight with regard to differing perspectives on the need for advocacy, issues related to social justice (employment, housing, relationships, etc.…”
Section: Life Span Identity Development and Age Cohortsmentioning
confidence: 99%
“…In terms of sexuality, half of the respondents were aware of same sex attraction in their adolescence or young adulthood and half of the respondents became aware in mid or later life. The major source of the stress for many of the respondents, but not all, could be summarized by the experience of silence (Parks, 1999).…”
Section: Experiences Of Stressmentioning
confidence: 99%
“…Although there appears to be a biological basis for same-sex attraction (for a review, see Rahman & Wilson, 2003), each individual who experiences this attraction will likely develop a distinct sexual identity due in part to the influence of such cultural factors. For example, in interviews with lesbian participants from varying age groups, Parks (1999) found that participants' sexual identity development, including the timing and the meanings ascribed to developmental events such as coming out, was related to the social and cultural context in which participants developed. Thus, contextual factors, including the effects of the media, should be considered when studying GLB identity.…”
mentioning
confidence: 99%